2019
DOI: 10.4148/1051-0834.2193
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Evaluations of Genetically Modified Food Messages

Abstract: Consumers are concerned about the risks related to genetically modified (GM) food, and there is a need for agricultural communicators and educators to address those concerns. The purpose of this study was to explore Florida residents' latitudes of acceptance, rejection, and noncommitment toward GM food messages. The findings from this study can be used to guide communication and education campaigns for GM food. An online survey was distributed to a non-probability sample of 500 Florida residents to fulfill the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In all conditions, an anonymous Twitter user (named Tyler Johnson 6 ) claimed that scientists “know” GMOs are not safe to eat and shared a meme claiming that most scientists say GMOs are UNSAFE with a picture of a syringe and the phrase “NO GMO” (see the Supplemental Appendix). This claim was specifically chosen because large numbers of people think that “potential risks of GM food related to health have not been adequately investigated” (Ruth & Rumble, 2019, p. 7). In the “Misinformation” condition, there are no responses to this tweet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all conditions, an anonymous Twitter user (named Tyler Johnson 6 ) claimed that scientists “know” GMOs are not safe to eat and shared a meme claiming that most scientists say GMOs are UNSAFE with a picture of a syringe and the phrase “NO GMO” (see the Supplemental Appendix). This claim was specifically chosen because large numbers of people think that “potential risks of GM food related to health have not been adequately investigated” (Ruth & Rumble, 2019, p. 7). In the “Misinformation” condition, there are no responses to this tweet.…”
Section: Methodsmentioning
confidence: 99%
“…Genetically modified foods consist of foods that have been altered in some way using “technologies used by seed breeders/scientists to make an intentional change to an organism’s DNA in order to promote a desired trait” (Ruth & Rumble, 2019, p. 6). Scientific opinion on the safety of GMF for human consumption is clear: In a 2015 survey of scientist members of the American Association for the Advancement of Science, 88% of respondents indicated that genetically modified foods were safe to eat (Pew Research Center, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2015, only 37% of U.S. consumers believed that ingredients from genetically engineered crops were safe for consumption, while 88% of scientist members of the American Association for the Advancement of Science considered human consumption safe [Funk, Rainie & Page, 2015]. We also know that U.S. consumers oppose statements about the safety of genetically engineered food for human consumption when compared to other statements about the advantages and disadvantages of the technology [Ruth & Rumble, 2019].…”
Section: Contextmentioning
confidence: 99%
“…For example, 44% of consumers in the same study said they disapprove of GM animal-sourced food products (Hallman et al, 2016). Results of a GM food messaging study by Ruth and Rumble (2019) found that Florida residents' views most align with statements that GM foods "have not been adequately investigated" and that GM foods "might be riskier to consume than traditional food" (p. 10). In an article summarizing GM knowledge worldwide, Wunderlich and Gatto (2015) reported findings of low consumer knowledge about GM products (Aleksejeva, 2014;Turker et al, 2013, Jurkiewicz et al, 2014 and GM knowledge varies by country (McGarry et al, 2012).…”
Section: Consumer Knowledge and Perceptions About Gm Food (All Ages)mentioning
confidence: 99%